Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I need solve this integral, and I tried various methods of solving and did not get it. The integral is:

$$\frac{1}{2\pi}\int_{0}^{2\pi}\frac{1}{1-2t\cos\theta +t^2}d\theta,$$

where $t$ is a positive integer.

share|improve this question
6  
An integral of a rational function of sine and cosine can always be transformed to an integral of a rational function by the substitution $u=\tan(\theta/2)$. –  Gerry Myerson Oct 11 '12 at 12:21
    
$2t\pi/(t^2-1)^{3/2}$ –  i. m. soloveichik Oct 11 '12 at 19:29
add comment

4 Answers

This is the famous Poisson kernel (see http://en.wikipedia.org/wiki/Poisson_kernel). For example, ${\displaystyle \frac{1}{1 - 2t\cos\theta + t^2} = {1 \over 1 - t^2}Re\bigg(\frac{1 + te^{i\theta}}{1 - te^{i\theta}}\bigg)}$, so you're looking for the real part of $${1 \over 2\pi(1 - t^2)}\int_0^{2\pi}{\frac{1 + te^{i\theta}}{1 - te^{i\theta}}}d\theta$$ As a complex integral this is $${1 \over 2\pi i(1 - t^2)}\int_{|z| = 1}\frac{1 + tz}{z(1 - tz)}\,dz$$ By the Cauchy integral formula this evaluates to $${1 \over 1 - t^2}$$ This is already real, so this is also the real part which is your answer.

share|improve this answer
1  
+1 for the Poisson kernel. –  Jack Oct 12 '12 at 3:08
add comment

It is easier to use techniques from complex variables (residue theorem), substitute $ \cos(\theta) = \frac{z+\frac{1}{z}}{2} \,$ where $ z=\exp{(i\theta)}$ and integrate

$$ \frac{1}{2\pi}\oint_{|z|=1}\frac{1}{1-2t\frac{z+\frac{1}{z}}{2} +t^2}d\theta = \dots $$

share|improve this answer
    
@Patricia thanks –  Patrícia Tempesta Oct 11 '12 at 17:44
    
@PatríciaTempesta: You are welcome. –  Mhenni Benghorbal Oct 11 '12 at 20:45
    
Nice and simple (+1) –  Chris's sis Feb 26 '13 at 22:35
add comment

$$\frac{1}{1-2t\cos \theta +t^2}=\frac 1{1+t^2-2t\frac{(1-\tan^2\frac{\theta}2)}{(1+\tan^2\frac{\theta}2)}}$$

$$=\frac{\sec^2\frac{\theta}2}{(1+t^2)(1+\tan^2\frac{\theta}2)-2t(1-\tan^2\frac{\theta}2)}=\frac{\sec^2\frac{\theta}2}{(1-t)^2+\tan^2\frac{\theta}2(1+t)^2}$$

$$=\frac1{(1+t)^2}\frac{\sec^2\frac{\theta}2}{(\frac{1-t}{1+t})^2+\tan^2\frac{\theta}2}$$

If $f(\theta)=\frac{1}{1-2t\cos \theta +t^2}, f(2\pi-\theta)=f(\theta)$,

So, $\int_{0}^{2\pi}f(\theta)d\theta=2\int_{0}^{\pi}f(\theta)d\theta$

$$I=\frac{1}{2\pi}\int_{0}^{2\pi}\frac{1}{1-2t\cos\theta +t^2}d\theta =\frac{1}{\pi}\int_{0}^{\pi}\frac{1}{1-2t\cos\theta +t^2}d\theta,$$

$$=\frac{1}{\pi(1+t)^2}\int_{0}^{\pi}\frac{\sec^2\frac{\theta}2}{(\frac{1-t}{1+t})^2+\tan^2\frac{\theta}2}d\theta$$

Now we can put $z=\tan \frac{\theta}2$ in the given problem, if $\theta=0,z=0$ and if $\theta=\pi,z=∞$ and $dz=\frac{\sec^2\frac{\theta}{2}d\theta}{2}$

So, $$I=\frac{1}{\pi(1+t)^2}\int_{0}^{∞}\frac{2dz}{(\frac{1-t}{1+t})^2+z^2}$$

$$=\frac{2}{\pi(1-t^2)} \tan^{-1}{\frac{(1+t)z}{1-t}} \mid_{0}^{∞}$$

At $z=0, \tan^{-1}{\frac{(1+t)z}{1-t}}=0$ if $t \ne 1$

At $z=∞, \tan^{-1}{\frac{(1+t)z}{1-t}}=\frac{\pi}2$ if $ \frac{1+t}{1-t}>0 $ or if $ \frac{(1+t)(1-t)}{(1-t)^2}>0$ or if $1-t^2>0$ or if $-1< t< 1$

At $z=∞, \tan^{-1}{\frac{(1+t)z}{1-t}}=-\frac{\pi}2$ if $t>1$ or $t<-1$

share|improve this answer
1  
How is this any better than just doing that substitution in the first place, as in my comment to the question? –  Gerry Myerson Oct 11 '12 at 12:33
    
@GerryMyerson, I've just showed to simplify the given expression to tangent ratio. –  lab bhattacharjee Oct 11 '12 at 12:36
    
@GerryMyerson, I thought, manipulation with fractional angle is less clear and error-inducing. –  lab bhattacharjee Oct 11 '12 at 12:41
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.